Bimetallic Ag–Au alloy nanocubes for SERS based sensitive detection of explosive molecules. (6th October 2020) - Kumar, Govind; Soni, R K
Abstract: We have fabricated Ag–Au alloy nanocubes using the galvanic replacement of silver nanocubes by aqueous HAuCl4 and investigated their morphological, structural, compositional and optical properties. The inter-diffusion between silver and gold at 100 °C leads to the formation of Ag–Au alloy nanocubes with hollow interiors. A broad tuning of the surface plasmon resonance (SPR) wavelength from 624 nm to 920 nm is obtained with the varying volume of HAuCl4 . When excited at wavelength 785 nm, the bimetallic Ag–Au nanocubes with pinholes exhibit two-fold Raman intensity enhancement compared to pristine Ag nanocubes. The surface-enhanced Raman spectroscopy (SERS) substrate prepared with Ag–Au alloy nanocubes shows high-intensity enhancement factor of 1.9 × 10 7 for 11.2 wt% Au content. The SERS-active Ag–Au alloy nanocubes substrates were exploited for the detection of two explosive molecules; p-nitrobenzoic acid (PNBA) and picric acid (PA). Remarkable detection sensitivity and ultra-low detection limit of 1.7 × 10 –14 M for PNBA and 4.1 × 10 –11 M for PA were obtained, demonstrating the very high SERS detection capabilities of the as-prepared substrate.